2011
DOI: 10.1016/j.ydbio.2010.09.023
|View full text |Cite
|
Sign up to set email alerts
|

CYP18A1, a key enzyme of Drosophila steroid hormone inactivation, is essential for metamorphosis

Abstract: Ecdysteroids are steroid hormones, which coordinate major developmental transitions in insects. Both the rises and falls in circulating levels of active hormones are important for coordinating molting and metamorphosis, making both ecdysteroid biosynthesis and inactivation of physiological relevance. We demonstrate that Drosophila melanogaster Cyp18a1 encodes a cytochrome P450 enzyme (CYP) with 26-hydroxylase activity, a prominent step in ecdysteroid catabolism. A clear ortholog of Cyp18a1 exists in most insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
171
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(189 citation statements)
references
References 52 publications
9
171
1
1
Order By: Relevance
“…7D). Consistent with this, previous works revealed that progression through metamorphosis requires 20E inactivation, an enzymatic reaction catalysed by Cyp18A1 (Guittard et al, 2011;Rewitz et al, 2010). These observations underscore the notion that the transient increase of ecdysone titres is as critical as the inactivation/clearance of the hormone.…”
Section: Dhr3 Mediates a Feedback Control On Steroid Biosynthesissupporting
confidence: 84%
“…7D). Consistent with this, previous works revealed that progression through metamorphosis requires 20E inactivation, an enzymatic reaction catalysed by Cyp18A1 (Guittard et al, 2011;Rewitz et al, 2010). These observations underscore the notion that the transient increase of ecdysone titres is as critical as the inactivation/clearance of the hormone.…”
Section: Dhr3 Mediates a Feedback Control On Steroid Biosynthesissupporting
confidence: 84%
“…The E22O-expressing transgenic D. melanogaster were, however, all embryonic lethal irrespective of the GAL4 driver lines used. These results were in contrast to those of the ecdysteroid 26-hydroxylase (cyp18A1)-expressing flies, where the time of death changed from the embryonic stage to the last larval instar stage depending on the GAL4 driver line used for crossing (21). Thus, contrary to our expectation, the E22O gene appears too strong to use in transgenic flies, suggesting that mutations to moderate the enzymatic activity of E22O may be necessary for its transgenic use.…”
Section: Discussioncontrasting
confidence: 97%
“…So far, four ecdysteroid inactivation enzymes have been identified in insects (18 -23). Mutations in or knockdown of those genes interfered with insect metamorphoses (21)(22)(23), indicating that both synthesis and inactivation of ecdysteroids are essential for the normal development of insects.…”
mentioning
confidence: 99%
“…Once the larval-larval transition or the moulting process is completed, the ecdysteroids must be quickly cleared to ensure the appropriate growth at each programmed life stage. The removal of the ecdysteroids requires two processes: the inactivation of existing ecdysteroids by enzymes such as CYP18A1 (Guittard et al 2011) and the suppression of the biosynthesis of the new ecdysteroids. Several ways of inactivating the existing ecdysteroids such as hydroxylation and conjugation have been identified (Meister et al 1985;You 2004), suggesting that ecdysteroid inactivation processes are redundant in animals to ensure the accurate "fall" of active hormones.…”
Section: Discussionmentioning
confidence: 99%